Zmiany w aksjologii polskiego street artu podczas pandemii COVID-19 - Sławek-Czochra, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
This article aims to show the values contained in Polish street art during the COVID-19 pandemic and the changes in their system. The research material consists of photographs of 100 examples of street visualisations obtained by typing keywords into an Internet search engine. The comparative material consists of works from 2008. A content analysis of the research material in terms of the values contained in street art during the COVID-19 pandemic showed that the pandemic knocked societies out of their natural rhythm of functioning and significantly affected the value system of street artists. In 2021, community, a sense of togetherness, life, physical and mental health, physical fitness, willingness to sacrifice and sacrifice, a sense of service, wisdom and knowledge, optimism and hope, and openness to other cultures, tolerance and universalism were at the top of the value system. These transformations can be explained by the scarcity hypothesis.